Influence of different breathing frequencies on the severity of inspiratory muscle fatigue induced by high-intensity front crawl swimming - Jakovljevic, D. G.; McConnell, A. K. (The Journal of Strength and Conditioning Research, 2009)
The aim of the present study was to assess the influence of 2 different breathing frequencies on the magnitude of inspiratory muscle fatigue after high-intensity front crawl swimming. The influence of different breathing frequencies on postexercise blood lactate ([La]) and heart rate (HR) was also examined. Ten collegiate swimmers performed 2 × 200-m front crawl swims at 90% of race pace with the following breathing frequencies: 1) 1 breath every second stroke (B2), and 2) 1 breath every fourth stroke (B4). Maximal inspiratory pressure (PImax) was measured at the mouth from residual volume before (baseline) and after swimming, in a standing position. The HR and [La] were assessed at rest and immediately at the cessation of swimming. The PImax decreased by 21% after B4 and by 11% after B2 compared with baseline (p < 0.05). The [La] was lower by 15% after B4 than after B2 (p < 0.05). The HR was not significantly different between B2 and B4. These data suggest that there is significant global inspiratory muscle fatigue after high-intensity swimming. Inspiratory muscle fatigue is, however, greater when breathing frequency is reduced during high-intensity front crawl swimming. Respiratory muscle training should be used to improve respiratory muscle strength and endurance in swimmers.